pH Metric Study of Ternary Complexes of Co(II) with Mercaptosuccinic Acid, 2-Mercaptopropionyl Glycine and Amino Acids - ZINE, A.M.; NAGRE, H.B.; KAYANDE, D.D. (Asian Journal of Chemistry, 2010)
The formation and stability constants of ternary complexes of Co(II) with sulphur containing ligands such as 2-mercaptopropionyl glycine, mercaptosuccinic acid (L1) and glycine (gly), alanine (ala), valine (Val) (L2) has been investigated potentiometrically. The stability constants are reported at 26 ± 0.5ºC in 0.1 M (NaClO4) ionic strength and compared with stabilities of corresponding Co(II)-amino acids binary complexes. The Δ log K values obtained are positive favoured the formation of ternary complexes.